Understanding of phraseology. - Yusupova Manzura Kurbanovna (Zien Journals, 2023)
Phraseologism, phraseological unit, phraseme - a common name for stable (stable) connections consisting of two or more words, which are semantically related to each other or equivalent to a sentence, which are used in a figurative sense as a whole and are not divided. Phraseologisms, unlike syntactic structures similar to them in form, do not arise by free choice and replacement of words in speech, but are used as pre-prepared material with a meaning and specific lexicogrammatical content, that is, it is impossible to exclude or leave out any part of the structure of Phraseologisms: the seed of an ango, barley to beat raw, to count dumplings as raw, to leave without fitting in the skin, to fly away, to fall in the place of the day, with an open hand, with a heavy ear, and other Phraseologisms have norms and methods of historical use, and their meanings are clarified in a certain speech process.
Keywords: Phraseological combinations; phraseologisms; phrase; linguistics